2002
DOI: 10.1114/1.1476016
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Quantification of Blood Flow and Wall Shear Stress in the Human Abdominal Aorta During Lower Limb Exercise

Abstract: Magnetic resonance (MR) imaging techniques and a custom MR-compatible exercise bicycle were used to measure, in vivo, the effects of exercise on hemodynamic conditions in the abdominal aorta of eleven young, healthy subjects. Heart rate increased from 73 +/- 6.2 beats/min at rest to 110 +/- 8.8 beats/min during exercise (p<0.0001). The total blood flow through the abdominal aorta increased from 2.9 +/- 0.6 L/min at rest to 7.2 +/- 1.4 L/min during exercise (p <0.0005) while blood flow to the digestive and rena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
109
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(117 citation statements)
references
References 28 publications
6
109
2
Order By: Relevance
“…In the abdominal aorta, a correlation between atherosclerosis and areas of low wall shear stress has been elucidated with prior autopsy (2,7,27,31,39) and experimental studies (5,16,19,20,22,32). Specifically, Cornhill et al (2) observed a high probability of occurrence of sudanophilic lesions along the posterior and lateral walls of autopsy specimens obtained from young, healthy males, whereas Roberts et al (27) and Glagov et al (21), and in vitro cell culture work has shown that oscillating shear can induce an inflammatory response, including an increase in reactive oxygen species (3,9,29).Conversely, elevated blood flow associated with exercise has been hypothesized to result in hemodynamic conditions that inhibit atherosclerosis, such as unidirectional laminar flow, increased wall shear stress, and enhanced transport of cholesterol from the vessel wall (11,18,32,33). It has been shown in vitro that the vascular endothelium can sense and respond to high shear environments by alignment in the direction of flow, upregulation of vasodilators and antioxidants, and downregulation of vasocontrictors, inflammatory molecules, and adhesion proteins (6,12,36,37), along with a variety of other responses that mediate the initiation and proliferation of disease.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the abdominal aorta, a correlation between atherosclerosis and areas of low wall shear stress has been elucidated with prior autopsy (2,7,27,31,39) and experimental studies (5,16,19,20,22,32). Specifically, Cornhill et al (2) observed a high probability of occurrence of sudanophilic lesions along the posterior and lateral walls of autopsy specimens obtained from young, healthy males, whereas Roberts et al (27) and Glagov et al (21), and in vitro cell culture work has shown that oscillating shear can induce an inflammatory response, including an increase in reactive oxygen species (3,9,29).Conversely, elevated blood flow associated with exercise has been hypothesized to result in hemodynamic conditions that inhibit atherosclerosis, such as unidirectional laminar flow, increased wall shear stress, and enhanced transport of cholesterol from the vessel wall (11,18,32,33). It has been shown in vitro that the vascular endothelium can sense and respond to high shear environments by alignment in the direction of flow, upregulation of vasodilators and antioxidants, and downregulation of vasocontrictors, inflammatory molecules, and adhesion proteins (6,12,36,37), along with a variety of other responses that mediate the initiation and proliferation of disease.…”
mentioning
confidence: 99%
“…It has been shown in vitro that the vascular endothelium can sense and respond to high shear environments by alignment in the direction of flow, upregulation of vasodilators and antioxidants, and downregulation of vasocontrictors, inflammatory molecules, and adhesion proteins (6,12,36,37), along with a variety of other responses that mediate the initiation and proliferation of disease. Although it is known that high shear forces are able to induce an atheroprotective phenotype on endothelial cells in culture, the lack of spatial and temporal quantification of physiological flow and shear stress patterns has hampered the use of more realistic flow conditions in biological experiments in vitro.Previous in vivo studies using noninvasive medical imaging techniques to quantify blood flow and wall shear stress during resting and exercise conditions in the human abdominal aorta have been limited to localized imaging planes (1,19,20,24,32) and have not fully described the three-dimensional distribution of hemodynamic conditions. Similarly, in vitro flow studies have traditionally been coupled with imaging techniques that only enable flow and shear stress quantification at specific sites (16,22).…”
mentioning
confidence: 99%
“…Tinken et al (37) showed that handgrip exercise caused a 60% increase in brachial artery shear rate. Taylor et al (35) showed that bicycle exercise led to 70 and 300% increases in shear stress in the supraceliac aorta and infrarenal aorta, respectively. In earlier work (14), we also found that unilateral femoral arteriovenous shunting in swine induced an increase in shear in the ipsilateral distal iliac artery, notwithstanding the dilation of the vessel.…”
Section: H900mentioning
confidence: 99%
“…DF and UF bulk flow generic waveforms were constructed after analysing blood flow measurements from non-invasive methods (e.g. magnetic resonance imaging, Doppler) at different sites in the arterial tree that have been identified as atherosusceptible or atheroprotected, including the coronary arteries [23][24][25][26][27][28]. The two generic constructed waveforms encompass the low-frequency fluid flow characteristics present at susceptible and protected sites while filtering out the high-frequency components characteristic of each specific site and individual human subject.…”
Section: Bulk Disturbed and Undisturbed Flow Waveformsmentioning
confidence: 99%